EFFECTIVE INTERNET AS A MARKETING ACTIVITY PLAN IN THE COMMERCIAL ENGINEERING COURSE OF THE PRIVATE UNIVERSITY OF THIS SUBSIDIARY CIUDAD DEL ESTE - Benitez, Oscar; Segovia, Jessica; Martínez , Elam; Úbeda, Gustavo; Maldonado, Elizabeth; Duarte, Álvaro (Revista Gênero e Interdisciplinaridade, 2023)
This article addresses the topic of digital marketing and how the effective Internet can be a successful marketing activity plan for the Commercial Engineering degree at the Universidad Privada del Este Branch Ciudad del Este. A descriptive and quantitative approach was used for the research, with a survey directed at the students of the program. The research design is characterized as transversal due to the time limitation established for its development. Research results are presented, including the analysis of social networks as powerful channels of communication and interaction with consumers, the application of highly targeted advertising campaigns that take advantage of the vast amount of data available online, and how the effective Internet It can be applied as a marketing activity plan in other university courses. The stages of the project are detailed, including the definition of objectives, the comprehensive review of existing literature, the selection of highly qualified researchers, the identification of necessary resources, and the creation of a carefully structured schedule of activities. It is concluded that digital marketing is a powerful tool for companies and that the effective Internet can be a successful marketing activity plan for the Commercial Engineering career at the Universidad Privada del Este Branch Ciudad del Este.